Interaksi Sosial Anak Nonreguler di SLB Zinnia Jakarta - Haryanti Jaya Harjani (Journal of Early Childhood Education (JECE), 2020)
The objective of this research is to describe study the social interaction of children with special needs such as autism spectrum disorders, down syndrome and mental retardation. This research is a qualitative research with a phenomenological method. The data analysis used is by the Miles and Huberman. Research data obtained from observations, interviews, and documentation. The research shows that: (1) Children's social interactions include communication, cooperation, and empathy have increased. Communication with peers is good even though it is limited, the child is able to work together in carrying out group assignments from his teacher (educator and therapist), as well as children learn empathy by giving some food that they brought to school with their friends; (2) Behavioral therapy learning model is used for education process; (3) The role of behavioral therapy learning model in the formation of social interactions of special needs children;(4) The role of parents, the environment home, school environment, and community environment in the formation of social interactions of non-regular children; (5) The success in this study is shown by changes in children’s behaviour in the home environment, school environment, and in the community environment.